2015
DOI: 10.1016/j.jcsr.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of controlled spine frames with energy-dissipating members

Abstract: Recently, various controlled rocking systems have been proposed in seismic design to prevent damage concentration and to achieve self-centering against a wide range of input ground motion intensities. However, several obstacles must be overcome before these systems can be applied to actual buildings; for example, the requirement for large, self-centering post-tensioned strands and special treatment at uplift column bases must be addressed. This paper proposes a non-uplifting spine frame system with energy-diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…It was determined that the seismic resistance (rotational inertia) increased in a square relationship with an increase in the plane size R ( R denotes the radial distance from the centre of gravity and one rotation corner at the bottom of the structure in a plane), whereas the seismic demand (the overturning moment) increased linearly with the plane size R. Therefore, as long as a high‐rise structure's plane size R was large enough, the structure could theoretically survive any earthquake and remain stable. In addition to reducing the seismic response by eliminating the connection between the superstructure and foundation, some scholars have proposed using the failure of the soil to form the rocking structure, and the impacts of the soil–foundation interaction on the seismic response characteristics of the rocking structure have been studied …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that the seismic resistance (rotational inertia) increased in a square relationship with an increase in the plane size R ( R denotes the radial distance from the centre of gravity and one rotation corner at the bottom of the structure in a plane), whereas the seismic demand (the overturning moment) increased linearly with the plane size R. Therefore, as long as a high‐rise structure's plane size R was large enough, the structure could theoretically survive any earthquake and remain stable. In addition to reducing the seismic response by eliminating the connection between the superstructure and foundation, some scholars have proposed using the failure of the soil to form the rocking structure, and the impacts of the soil–foundation interaction on the seismic response characteristics of the rocking structure have been studied …”
Section: Introductionmentioning
confidence: 99%
“…For the problem of a traditional rocking structure exhibiting great unpredictability in the seismic response process, many scholars have proposed effective measures to control them . Ma et al and Eatherton and Hajjar used replaceable fuses to consume seismic energy for improved safety and economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…e experimental results showed that spine systems can effectively reduce the concentration of deformations. Takeuchi et al [22] proposed a nonuplifting spine frame system with two replaceable BRBs at the bases of the frames to concentrate the major damage into the BRBs and prevent structural collapse. Chen et al [23] designed a tall steel-braced frame with segmental elastic trussed spines and a uniform story drift response can be found in this newly proposed system.…”
Section: Introductionmentioning
confidence: 99%
“…(B. A new controlled spine frame was proposed by the authors (T. Takeuchi et al 2015;X. Chen et al 2017), as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%